Pastoral care and the agony of female singleness in the African christian context - M.E. Baloyi (In die Skriflig, 2010)
In our society the norm is thatevery adult should get married one day. This could imply thatunmarried people do not feel welcome either in the community or the church. They may feel neglected or even like outcasts. It is a pity that the church, which also finds itself within the community, is composed of people who still continue to havethe kind of attitude that excludes singles, even inside church circles. While churches run programmes that have a strong emphasis on marriage and family life, nothing is being doneto address singleness and its related problems. As a result, singles often regard themselves as unimportant and worthless. This article is aimed at un-covering the role of the church through its leadership (pastors in particular) to assist and helpto redeem the damaged image and self-esteem that singles may have in their respective communities and churches. The article focuses on singles in the African church and society. It is crucial that a church programme of care and counselling be structured in order to minister to persons who are separated, divorced, widowed or never married for whatever reason.